A prestação de serviços à comunidade coletiva: novas práticas pedagógicas como alternativa à centralidade punitiva - Matos, Alice Vettorazzo Calil (2021)
This research investigates the experience of adolescents and professionals in the city of São Paulo in carrying out the socio-educational measure of Collective Community Services Provision - PSC, which is developed under a participatory and emancipatory perspective, as well as the process of political defense of this methodology by the Movement of Workers of Socio-educational Measures Services in Community Settings in the city of São Paulo. Initially the socio-educational measures are analyzed from their ruptures and continuities with the minoristic codes and with the Penal Code, showing how these devices - in particular the socioeducational measures and the adult alternatives to incarceration - constitute an advance in the guarantee of rights at the same time that, together with the social assistance policy, they can be understood as part of a political project necessary for the advancement of neoliberalism. This research shows that this dynamic goes back to the political-ideological conflicts that, historically, have marked the advances in guaranteeing the rights of adolescents and youth, and to the ambivalence of the mechanisms of accountability and punishment. Although the collective PSC does not resolve the ambiguous nature of the socio-educational measures, it contributes significantly to elevate their pedagogical character in line with what was thought about the socio-education in the Statute of the Child and Adolescent (ECA) and in the National System of Socio-Educational Care (SINASE). In order to understand this entire process, in addition to the bibliographical research, open interviews were conducted with adolescents and socio-educators who had contact with the collective PSC at the SMSE/MA, with professionals who participated in the debates on the elaboration of the ECA and SINASE and with the coordination of the Department of Child and Youth Executions (DEIJ) of the District of São Paulo. In addition to the testimonies of these actors, an analysis of the case file of an adolescent who complied with the aforementioned measure was also developed in order to capture the vision that the professionals working in the juvenile justice system have in relation to collective PSC, especially in the year 2018, when the debate about this methodology was fiercer